Security and Efficiency Challenges in Cloud-Integrated Wireless Sensor Networks: A Comprehensive Review (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Environmental monitoring, healthcare, smart cities, and industrial automation are just a few of the many applications that have seen the widespread use of Wireless Sensor Networks (WSNs). Issues with scalability, security, and data management arise from sensor nodes' limited resources, including power, computing power, and storage space. One approach is to combine WSNs with cloud computing, which offers elastic computing resources, large-scale storage, and the ability to do complex data analysis. Although there are numerous advantages to this technology, cloud-based WSNs still face challenges such as complex system architecture, decreased performance, and new security risks. Ensuring the safety and efficiency of WSN architectural design in a cloud environment is the primary emphasis of this work. Secure data transmission, robust authentication, and access control are the main tenets of the suggested architecture, which aim to shield sensor data from cyber attacks and illegal access. Also tuned for increased efficiency are cloud-based communication, data aggregation, and resource management. The architecture's goals include reducing data transmission times, increasing network longevity, enhancing system performance, and protecting data integrity and secrecy. To address one of the primary challenges in merging traditional and cloud WSNs, the model incorporates design principles of both efficiency and security. Building on previous work, this study proposes a novel architectural design for cloud-based wireless sensor networks that improves their scalability and flexibility. It also paves the way for future work in this area.